The Impact of Abdominal Liposuction on Abdominally Based Autologous Breast Reconstruction: A Systematic Review - Bond, Evalina S.; Soteropulos, Carol E.; Poore, Samuel O. (Archives of Plastic Surgery, 2022)
Prior abdominal liposuction can be viewed as a relative or absolute contraindication to abdominally based autologous breast reconstruction given concerns for damaged perforators and scarring complicating intraoperative dissection. This systematic review aims to explore the outcomes of abdominally based breast reconstruction in patients with a history of abdominal liposuction. A Preferred Reporting Items for Systematic Reviews and Meta-Analyses-guided literature search was conducted using PubMed, Scopus, and Web of Science from the earliest available date through June 2020. Deep inferior epigastric perforator, muscle-sparing transverse rectus abdominis musculocutaneous (TRAM), superficial inferior epigastric artery, and pedicled TRAM flaps were included for evaluation. Complications included total or partial flap loss, fat necrosis, seroma, delayed wound healing, and donor site complications. After inclusion criteria were applied, 336 nonduplicate articles were screened, yielding 11 for final review, representing 55 flaps in 43 patients. There was no instance of total flap loss, eight (14.5%) flaps developed partial loss or fat necrosis, three (5.4%) flaps had delayed wound healing, and two (4.6%) patients had donor site complications. Most authors (8/11) utilized some type of preoperative imaging. Doppler ultrasonography was the most used modality, and these patients had the lowest rate of partial flap loss or flap fat necrosis (8%), followed by those without any preoperative imaging (10%). In conclusion, this review supports that patients undergoing abdominally based autologous breast reconstruction with a history of abdominal liposuction are not at an increased risk of flap or donor site complications. Although preoperative imaging was common, it did not reliably decrease complications. Further prospective studies are needed to address the role of imaging in improving outcomes.
Keywords: autologous breast reconstruction; liposuction; suction assisted lipectomy; DIEP flap; MS-TRAM; pedicled TRAM